PELATIHAN PEMANFAATAN CANVA SEBAGAI SARANA PEMBUATAN BAHAN AJAR BERBASIS DIGITAL YANG KREATIF DAN INOVATIF DI SDN 1 CIUYAH LEBAK BANTEN - Holilah Holilah; Puspita Maelani; Solihin Solihin; Asep Yana Yusyama (LPPM Universitas Bina Bangsa, 2023)
Technological developments affect all aspects, including the educational aspect. The use of this technology can go hand in hand with how educators or teachers create a learning method so that it can affect the effectiveness of the learning process. SDN 1 Ciuyah Lebak Banten has facilities for using technology for learning, but this technology has not been utilized by teachers to be used in the learning process while the role of the teacher must continue to create creative and innovative learning methods, so that the knowledge that will be transferred to students can be successful. One of them is the use of Canva in the learning process. This service activity uses three stages, namely preparation, implementation and evaluation. As a result of this dedication, the use of Canva-based technology in learning provides knowledge and skills to teachers so that they can increase success in the learning process. The importance of training that supports teacher effectiveness in teaching should be gradual because it takes a lot of time to directly apply the use of Canva